A Simple Formula for the Polar Second Moment of Area of a Regular Skew-Symmetric Bolt Group - Irvine, H.M.; Bradfield, C.D. (Engineering Journal, 1979)
Some years ago the authors worked together for a London firm of consulting engineers on the design of long span bridges. There they encountered the problem of calculating the polar second moment of area of very large skew-symmetric bolt groups. At that time, the second author derived the results which appear as Eq. (5). Recently, the first author has simplified those results to obtain Eq. (10). The purpose of this paper is to derive both results.